Healthy Lifestyle and Its Importance for Human Health - Dumayeva , Zuxra; Baxromjonova , Munisa (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the key components of a healthy lifestyle, its impact on human health, and the formation of healthy living skills in modern society. The importance of physical activity, proper nutrition, and psychological stability is also scientifically substantiated.